The generation potential of the Bazhenov Formation and its stratigraphic analogues in the east of Western Siberia - Goncharov I. V. Ivan Vasilyevich; Samoylenko V. Vadim; Oblasov N. Nikolay; Fadeeva S. Svetlana; Krinin V. Vladimir; Volkov V. Vladimir (2011, 2011)
В фонде НТБ ТПУ отсутствует